SOSIALISASI PENTINGNYA MENJAGA KESEHATAN MENTAL REMAJA DI SMK PGRI 4 KOTA SERANG - Dewi Surani; Firly Noning; Lilis Siti Nurjanah; Ghaliyah Yasir; Radella Rumapea; Rahmila Tiva; Nurul Amanah (LPPM Universitas Bina Bangsa, 2024)
Mental or psychiatric disorders can be experienced by anyone, and require greater attention in society. The prevalence of mental health disorders characterized by symptoms such as depression and anxiety in people over 15 years of age is around 6.1% of Indonesia's population or equal to 11 million people. Based on this, community service in the form of socializing the importance of maintaining mental health in teenagers was carried out at one of the schools, namely PGRI 4, Vocational School Serang City. This socialization was carried out on May 15 2024 with a total of 30 students as respondents. The method used is descriptive quantitative with a cross-sectional approach. The stages of this socialization activity consist of planning, implementation and evaluation. The instruments used in this research are the Strengths and Difficulties Questionnaire (SDQ) and an evaluation questionnaire. The SDQ results showed that the strength score was within the normal limit and the difficulty score was at the borderline (37%) but peer problems were in an abnormal condition. This is due to a lack of socialization with peers both at home and at school. The provision of mental health material carried out by the